Solomon Islands : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that real GDP growth of Solomon Islands rose to an estimated 6 percent in 2006, driven by fish, palm oil production, and services. However, it is expected to ease to 5 1\2 percent in 2007, as a further escalation in logging will be likely offset by lower growth of fish and traditional crops. With the natural forest expected to be depleted within the next few years, structural reforms are necessary to generate higher sustainable growth, raise living standards, and reduce the economy's vulnerability to shocks.